2017
DOI: 10.1097/ico.0000000000001440
|View full text |Cite
|
Sign up to set email alerts
|

Topical Tacrolimus 0.03% for Maintenance Therapy in Steroid-Dependent, Recurrent Phlyctenular Keratoconjunctivitis

Abstract: Topical tacrolimus 0.03% was effective in maintaining long-term remission in patients with recurrent, steroid-dependent PKC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…TAC is mainly used clinically for treating various chronic allergic conjunctivitis conditions, including VKC, AKC, and giant papillary conjunctivitis 19. Several studies have shown that TAC plays an important role in the treatment of chronic allergic conjunctivitis, based on TAC’s effect in substantially reducing the symptom score by approximately 50% 20–26. In addition, the safety of long-term TAC application in the treatment of allergic conjunctivitis has also been verified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAC is mainly used clinically for treating various chronic allergic conjunctivitis conditions, including VKC, AKC, and giant papillary conjunctivitis 19. Several studies have shown that TAC plays an important role in the treatment of chronic allergic conjunctivitis, based on TAC’s effect in substantially reducing the symptom score by approximately 50% 20–26. In addition, the safety of long-term TAC application in the treatment of allergic conjunctivitis has also been verified.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several studies have shown that TAC plays an important role in the treatment of chronic allergic conjunctivitis, based on TAC's effect in substantially reducing the symptom score by approximately 50%. [20][21][22][23][24][25][26] In addition, the safety of long-term TAC application in the treatment of allergic conjunctivitis has also been verified. A study by Al-Amri et al, 27 using 0.1% topically applied TAC for treatment of AKC over 48 months, demonstrated the control and remission of the disease in the absence of other medications.…”
Section: Systematic Reviewmentioning
confidence: 92%
“…46 However, doxycycline and other tetracyclines should still not be used for PKC because a prolonged course of these agents is typically needed. Adjuvant steroid-sparing topical agents such as cyclosporine 17,22,42 or tacrolimus 43,47 may also be beneficial in some cases to control disease and reduce cumulative corticosteroid burden. The treatment of PKC principally should also address the underlying cause.…”
Section: Discussionmentioning
confidence: 99%
“…6 BKC treatments include topical and/or systemic medications targeting the clearance of meibomian gland secretion, 4,6,7 correction of ocular surface dysbiosis, 1,5,15,16 and reduction of ocular surface inflammation. 1,5,6,[17][18][19][20][21][22][23] Despite treatment, BKC is recurrent and chronic in nature, rendering pediatric patients vulnerable to detrimental and permanent visual impairment. Thus, long-term observation and management are critical to ensure full visual development in pediatric patients with BKC.…”
mentioning
confidence: 99%